New Generation Cardiac Contractility Modulation Device—Filling the Gap in Heart Failure Treatment - Tint, Diana (J Clin Med, 2019)
(1) Background: Heart failure (HF) is a major cause of morbidity and mortality throughout the world. Despite substantial progress in its prevention and treatment, mortality rates remain high. Device therapy for HF mainly includes cardiac resynchronization therapy (CRT) and the use of an implantable cardioverter-defibrillator (ICD). Recently, however, a new device therapy—cardiac contractility modulation (CCM)—became available. (2) Aim: The purpose of this study is to present a first case-series of patients with different clinical patterns of HF with a reduced ejection fraction (HFrEF), supported with the newest generation of CCM devices. (3) Methods and results: Five patients with a left ventricular ejection fraction (LVEF) ≤ 35% and a New York Heart Association (NYHA) class ≥ III were supported with CCM OPTIMIZER(®) SMART IPGCCMX10 at our clinic. The patients had a median age of 67 ± 8.03 years (47–80) and were all males—four with ischemic etiology dilated cardiomyopathy. In two cases, CCM was added on top of CRT (non-responders), and, in one patient, CCM was delivered during persistent atrial fibrillation (AF). After 6 months of follow-up, the LVEF increased from 25.4 ± 6.8% to 27 ± 9%, and the six-minute walk distance increased from 310 ± 65.1 m to 466 ± 23.6 m. One patient died 47 days after device implantation. (4) Conclusion: CCM therapy provided with the new model OPTIMIZER(®) SMART IPG CCMX10 is safe, feasible, and applicable to a wide range of patients with HF.